An in situ iodine-doped graphene/silicon composite paper as a highly conductive and self-supporting electrode for lithium-ion batteries. Issue 61 (7th August 2017) - Chen, Cheng; Wu, Mengqiang; Wang, Sizhe; Yang, Jian; Qin, Jingang; Peng, Zhi; Feng, Tingting; Gong, Feng
Abstract : A highly conductive, highly flexible, self-supporting, and binder-free rGO/Si composite paper with superior electrochemical performance was obtained via in situ iodine doping and used as electrodes for flexible LIBs. Abstract : A graphene/silicon composite paper is considered as a promising anode material for flexible batteries. Herein, a highly conductive, flexible, self-supporting, and binder-free graphene/Si composite paper has been prepared via in situ iodine doping and simultaneous reduction of a graphene oxide/silicon composite slice with a solution of hydrohalic (HI) acid as a reducing agent. The in situ iodine doping not only increases the electrical conductivity of the graphene/silicon composite paper, but also improves the strength of the graphene matrix; this results in high capacity and enhanced cycling stability. The in situ iodine-doped composite paper is used as a flexible, self-supporting, and binder-free electrode. The composite paper exhibits a stable capacity retention of 805 mA h g −1 after 100 cycles and an enhanced rate capability, which shows superior performance as compared to the common thermally reduced rGO/Si composites. The high flexibility and high conductivity as well as improved electrochemical performance of this binder-free self-supporting paper anode make it attractive for LIB applications in flexible storage devices.